Global, regional, and national sex differences in the global burden of tuberculosis by HIV status, 1990-2019: results from the Global Burden of Disease Study 2019 - Ledesma, Jorge R (ELSEVIER SCI LTD, 2023)
10.1016/S1473-3099(21)00449-7